Carbon nanomaterials synthesized using a spray pyrolysis method. (August 2015) - Huang, Wen-Ko; Chung, Kun-Ju; Liu, Yih-Ming; Ger, Ming-Der; Pu, Nen-Wen; Youh, Meng-Jey
Abstract: Carbon nanomaterials were synthesized using a spray pyrolysis chemical vapor deposition system (SPCVD). By varying the reaction temperature or flow rate of the carbon source, the structure or morphology of the synthesized carbon nanocoils (CNCs) can be controlled. A vertical chemical vapor deposition (CVD) furnace with a three-stage heating zone was employed to synthesize carbonaceous nanomaterials using nano-Pd catalysts at growth temperatures of 600, 700, and 800 °C. The morphology of the synthesized carbon products and the relationship between the carbon source concentration and its yield were evaluated. The results showed that CNCs formed at a lower temperature (600 °C), whereas straight carbon nanotubes were obtained at a higher temperature (700 or 800 °C). The structure and morphology of the carbonaceous samples were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Their graphite crystallinity was analyzed using Raman spectroscopy. When the three heating zones of the vertical CVD chamber were set to different temperatures, a unique nano-carbonaceous material with a special morphology similar to an octopus tentacle was formed. Highlights: Nano-Pd catalyzed carbon nanomaterial synthesis using a spray pyrolysis method. Several different morphologies can be obtained by varying growth temperature. Relation between C2 H2 concentration and the yield of carbon nano-coils was studied. A unique octopus-tentacle-like product was synthesized in a 3-heating-zone furnace.